Inhibition of Embryonic HSP 90 Function Promotes Variation of Cold Tolerance in Zebrafish - Han, Bingshe; Luo, Juntao; Jiang, Penglei; Li, Yan; Wang, Qiong; Bai, Yajing; Chen, Jing; Wang, Jian; Zhang, Junfang (Frontiers in Genetics, 2020)
Accumulating evidence indicates that heat shock protein 90 (HSP90) plays essential roles in modulation of phenotypic plasticity in vertebrate development, however the roles of HSP90 in modulation of cold tolerance capacity in fish are still unclear. In the present study, we showed that transient inhibition of embryonic HSP90 function by a chemical inhibitor or low conductivity stress promoted variation of cold tolerance capacity in adult zebrafish. Further work showed that embryonic HSP90 inhibition enhanced cold tolerance in adult zebrafish could be transmitted to their offspring. RNA-seq data showed that embryonic HSP90 inhibition enhanced cold tolerance involves variation of gene expression related to proteasome, lysosome, autophagy, and ribosome. Experiments with zebrafish ZF4 cells showed that two differentially expressed genes atg9b and psmd12 were up-regulated by radicicol treatment and provided protective roles for cells under cold stress, indicating that up-regulation of autophagy and proteasome function contributes to enhanced cold tolerance. The present work sheds a light on the roles of HSP90 in regulation of phenotypic plasticity associated with thermal adaptation in fish.